Investigating Maxillary Sinus and Buccal Bone Biometrics via Cone Beam Computed Tomography (CBCT) in an Iranian Sample - Shahi, Shahriar; Ghanbaran , Sahar; Movahed, Emad; Moharrami, AmirMohammad; Nekouei, Afsaneh; Mohammadikhah, Meysam; Ghadimi, Shaghayegh (Galen Medical Journal, 2025)
Background: The maxillary sinus’s close anatomical relationship with posterior teeth roots presents significant challenges in dental and surgical procedures, with variations in sinus morphology influencing clinical outcomes. This study aimed to evaluate maxillary sinus biometrics and buccal bone thickness using Cone Beam Computed Tomography (CBCT) in an Iranian population. Materials and Methods: A retrospective analysis of 210 CBCT scans was conducted, measuring root apex proximity to the maxillary sinus floor (MSF) and buccal cortical bone thickness. Results: Findings revealed that 53.06% of right third molar roots protruded into the MSF, while only 2% of left first premolars did. The mesiobuccal root of the third molar had the shortest distance to the MSF (-1.38 ± 0.89 mm), whereas the palatal root of the first premolar was farthest (9.81 ± 3.93 mm). Buccal bone thickness was thinnest at the first premolar (1.21 mm) and thickest at the third molar palatal root (13.23 mm), with significant differences observed among molar roots. Conclusion: These findings underscore the importance of CBCT in preoperative planning to minimize complications during apical surgery and implant placement, particularly in cases involving posterior maxillary teeth.